Preventing Extremism with Extremists: A Double-Edged Sword? An Analysis of the Impact of Using Former Extremists in Danish Schools - David Parker; Lasse Lindekilde (MDPI AG, 2020)
Governments across the West have invested significant resources in preventing radicalization, and strategies to prevent and counter violent extremism (P/CVE) are increasingly prominent within wider counter-terrorism policies. However, we know little about their effects, especially about projects that utilize former extremists to counter extremist narratives and increase critical thinking. Despite the prominence of interventions utilizing "formers", there are almost no systematic, scientific evaluations of these programs. The lack of evaluation is problematic given the recognized risks and negative effects of using formers to address other social issues, such as crime prevention. This paper presents findings from the largest study to date of the effects of using former extremists to prevent violent extremism. Based on a randomized controlled effect evaluation with 1931 Danish youths, it highlights significant successes, including reducing the perceived legitimacy of political violence, as well as negative effects, including a small decrease in political tolerance. Overall, the findings suggest a need for cost-benefit analyses of P/CVE initiatives, weighing the benefits against the risks.